2013
DOI: 10.1177/2050312113494974
|View full text |Cite
|
Sign up to set email alerts
|

Should we think about wrist extensor after flexor tendon repair?

Abstract: Objective:To evaluate the activity of wrist extensor muscle, correlating with wrist motion during gripping after flexor tendon repair.Design:Cross-sectional clinical measurement study.Setting:Laboratory for biomechanics and rehabilitation.Subjects:A total of 11 patients submitted to rehabilitation by early passive motion of the fingers with wrist flexion position were evaluated after 8 weeks of fingers flexor tendon repair and 11 healthy volunteers, all ranging from 20 to 37 years of age.Intervention:Volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Even with a wide variety of studies, we can observe that there is still no consensus on the positioning of electrodes and the influence of different wrist angles in the palmar grip task 32,34,38,39 . The muscular physiological processes can be analyzed by electromyographic signal during standardized activities.…”
Section: Discussionmentioning
confidence: 99%
“…Even with a wide variety of studies, we can observe that there is still no consensus on the positioning of electrodes and the influence of different wrist angles in the palmar grip task 32,34,38,39 . The muscular physiological processes can be analyzed by electromyographic signal during standardized activities.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used surface electromyography as a muscle activation assessment tool 4 with electrode sites defined through palpation, 35 analysing the ECRB/L, EDC and ECU as synergistic muscles of the wrist and hand, which are often affected by the inflammatory and/or degenerative process in LE. There are many studies in the literature that use surface EMG analyses on forearm muscles; 6,3843 even so, there is still no consensus on electrode placement. In addition, we conducted an initial pilot study and found high test–retest reliability of the positioning ( r = 0.81).…”
Section: Discussionmentioning
confidence: 99%
“…The upper limb is an important segment for contact with the external environment, and the joint sensorimotor system and the peripheral sensory nerve fibers are essential for proper movement skills, enabling to perform the activities of daily living (ADLs) 1-3 such as grasping and handling of objects, feeding or dressing, directly depending on the proper stability of the wrist 4 , mainly represented by the synergistic action of the extensor and flexor muscles of the wrist and fingers 5,6 . While performing a functional task with the fingers, the stabilizers of the wrist, elbow and shoulder help prevent compensatory movements and, therefore, are closely related 7 .…”
Section: Introductionmentioning
confidence: 99%